2020
DOI: 10.1055/a-1231-4758
|View full text |Cite
|
Sign up to set email alerts
|

A rare complication of ERCP: duodenal perforation due to biliary stent migration

Abstract: Background and study aims Perforation of the duodenal wall opposing the major papilla due to a migrated pancreatobiliary stent rarely has been described in the literature as a complication of endoscopic retrograde cholangiopancreatography (ERCP). Factors associated with perforation from migrated stents from ERCP are unknown. Patients and methods This was a retrospective, observational study. Patients were identified from January 1, 1994 to May 31, 2019 in a prospectively maintained ERCP database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Colonic perforation is a rare complication of biliary stenting. Reviewing reported cases of colonic perforations of biliary stents from 2000 to 2022 (Table 1 ), we found that unlike in duodenal perforation, which carries a high risk of mortality, 6 , 7 mortality in reported cases of colonic perforation is low (1 of 32). Of note, only 1 perforation was confirmed to be due to a pigtail stent while 31 of 32 perforations were caused by straight stents (25 of 32) or the type of stent was not mentioned (5 of 32).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Colonic perforation is a rare complication of biliary stenting. Reviewing reported cases of colonic perforations of biliary stents from 2000 to 2022 (Table 1 ), we found that unlike in duodenal perforation, which carries a high risk of mortality, 6 , 7 mortality in reported cases of colonic perforation is low (1 of 32). Of note, only 1 perforation was confirmed to be due to a pigtail stent while 31 of 32 perforations were caused by straight stents (25 of 32) or the type of stent was not mentioned (5 of 32).…”
Section: Discussionmentioning
confidence: 88%
“…Although stent migration is not uncommon, serious complications due to this are rare. Duodenal perforation vis-à-vis of the papilla by straight biliary stents ranges from 1 in 2,293 6 to 2.1%. 7 The majority was managed with endoscopic removal and closure, with however high mortality (3 of 11 6 vs 4 of 13 cases 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1 , 13 cases, including our case, of endoscopic closure using an OTSC for gastrointestinal perforation due to bile duct stent migration have been reported thus far [ 6 , 12 15 ]. Endoscopic closure was successful in all 13 cases, and OTSC closure was considered safer than clip closure.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation due to displacement of the biliary stent can occur mainly in the duodenum and in other parts of the small intestine and the colon [ 5 – 9 ]. In recent years, endoscopic closure of gastrointestinal perforations using an over-the-scope clip (OTSC) has been shown to be effective with a high success rate [ 6 , 10 14 ]. Here, we have reported a case of sigmoid colon perforation caused by a bile duct stent that was treated conservatively by endoscopic closure using an OTSC.…”
Section: Introductionmentioning
confidence: 99%